2020
DOI: 10.1371/journal.pone.0221843
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of GPS collars on the activity, behavior, and adrenal response of scimitar-horned oryx (Oryx dammah)

Abstract: GPS collars have revolutionized the field of animal ecology, providing detailed information on animal movement and the habitats necessary for species survival. GPS collars also have the potential to cause adverse effects ranging from mild irritation to severe tissue damage, reduced fitness, and death. The impact of GPS collars on the behavior, stress, or activity, however, have rarely been tested on study species prior to release. The objective of our study was to provide a comprehensive assessment of the shor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…We note that the survival of such animals is believed to be especially sensitive to the proportion of successful hunts (cf. (Scantlebury et al 2014)) which calls for critical evaluation of performance between tag-wearing and unequipped animals, or animals equipped with tags of different masses (cf. (Wilson et al 1986)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the survival of such animals is believed to be especially sensitive to the proportion of successful hunts (cf. (Scantlebury et al 2014)) which calls for critical evaluation of performance between tag-wearing and unequipped animals, or animals equipped with tags of different masses (cf. (Wilson et al 1986)).…”
Section: Discussionmentioning
confidence: 99%
“…(Rosen et al 2017;Kay et al 2019)), drag is negligible in terrestrial (though not aerial) systems even though tag detriment in terrestrial animals has been widely reported and is multi-facetted (Murray & Fuller 2000). Reported issues range from minor behavioural changes (Stabach et al 2020) through skin-, subcutaneous-and muscle damage with ulceration (Krausman et al 2004;Hopkins & Milton 2016) to reduced movement speed (Brooks et al 2010) and dramatically increased mortality (Rasiulis et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the frequency with which the animals shake, scratch or groom themselves or other individuals may indicate direct effects of the collar. Scimitar-horned oryx ( Oryx dammah ) showed for instance short term increase of head shaking immediately after being fitted with GPS collars [ 27 ]. Also captive red foxes ( Vulpes vulpes ) showed significant increases in the behaviours rubbing and shaking after being fitted with telemetry collars.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, quantifying behavioral responses post-capture can provide species-specific information on altered behavior and inform future studies (Dechen Quinn et al, 2012). For example, Stabach et al (2020) examined effects of GPS collar deployment on scimitar-horned oryx (Oryx dammah) to quantify the short-term responses in activity, behavior, and stress levels, and the length of time before these effects subsided. Visual observation showed headshaking significantly increased post-capture but returned to pre-capture levels within 3 days, and random forest classification of tri-axial accelerometer data indicated a 480% increase in headshaking compared to stable baseline levels that resumed after 24 hours.…”
Section: Identification Of Altered Behavior Post-capturementioning
confidence: 99%
“…Visual observation showed headshaking significantly increased post-capture but returned to pre-capture levels within 3 days, and random forest classification of tri-axial accelerometer data indicated a 480% increase in headshaking compared to stable baseline levels that resumed after 24 hours. Using piecewise regression, Stabach et al (2020) found that fecal glucocorticoid metabolite levels were elevated for five days following collar deployment, suggesting a stress response, before returning to baseline levels.…”
Section: Identification Of Altered Behavior Post-capturementioning
confidence: 99%